Reduced treatment frequencies with bumped kinase inhibitor 1369 are effective against porcine cystoisosporosis - Shrestha, Aruna (Int J Parasitol Drugs Drug Resist, 2020)
Bumped kinase inhibitors (BKIs) are a new class of antiprotozoal drugs that target calcium-dependent protein kinase 1 (CDPK1) in various apicomplexan parasites. A multiple dose regimen of BKI 1369 has been shown to be highly effective against Cystoisospora suis (syn. Isospora suis), the causative agent of neonatal porcine coccidiosis. However, multiple dosing may not be widely applicable in the field. The present study aimed to determine the efficacy of reduced treatment frequencies with BKI 1369 against porcine cystoisosporosis in vitro and in vivo. Pre-incubation of sporozoites with BKI 1369 completely failed to inhibit the infection in vitro unless treatment was prolonged post-infection. Notably, a single treatment of infected cell cultures 2 days post-infection (dpi) resulted in a significant reduction of merozoite replication. In an experimental infection model, treatment of suckling piglets experimentally infected with C. suis 2 and 4 dpi with 20 mg BKI 1369/kg body weight completely suppressed oocyst excretion. A single treatment on the day of infection or 2 dpi suppressed oocyst excretion in 50% and 82% of the piglets and reduced the quantitative excretion in those that shed oocysts by 95.2% and 98.4%, respectively. Moreover, a significant increase in body weight gain and reduced number of diarrhea days were observed in BKI 1369 treated piglets compared to the control piglets, irrespective of time points and frequencies of treatment. Given that reduced treatment frequencies with BKI 1369 are comparable in efficacy to repeated applications without any adverse effects, this could be considered as a practical therapeutic alternative against porcine cystoisosporosis.